Advanced materials and technologies in construction, energy production and waste treatment selected, peer reviewed papers from the International Scientific Conference "Advanced Materials and Technologies for Energy Efficiency and Sustainable Development", April 27-29, 2016, Saint Petersburg, Russia - Vatin, Nikolai; Murgul, Vera (Materials Science Forum ;, 2016)
This collection of papers will be useful of the wide range of engineers and researchers in area of civil and industrial constraction, energy production and treatment of wastes.